2021
DOI: 10.1186/s12944-021-01446-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of ASM/Cer/TXNIP signaling module in the NLRP3 inflammasome activation

Abstract: Background This study aimed to explore the effects of ceramide (Cer) on NLRP3 inflammasome activation and their underlying mechanisms. Methods Lipopolysaccharide (LPS)/adenosine triphosphate (ATP)-induced NLRP3 inflammasome activation in J774A.1 cells and THP-1 macrophages was used as an in vitro model of inflammation. Western blotting and real-time PCR (RT-PCR) were used to detect the protein and mRNA levels, respectively. IL-1β and IL-18 levels w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Consistent with our finding, Jiang et al. ( 71 ) recently reported that lipopolysaccharide/ATP-induced increase of ASM activity and accumulation of ceramide is attributed to TXNIP/NLRP3 inflammasome activation in J774A.1 cell and THP-1 macrophages. Koka et al.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our finding, Jiang et al. ( 71 ) recently reported that lipopolysaccharide/ATP-induced increase of ASM activity and accumulation of ceramide is attributed to TXNIP/NLRP3 inflammasome activation in J774A.1 cell and THP-1 macrophages. Koka et al.…”
Section: Discussionsupporting
confidence: 93%
“…TXNIP binding to NLRP3 inflammasome is involved in regulating inflammation [ 14 ], besides, inflammation plays a key role in vascular calcification. In order to verify TXNIP effect on the expression of NLRP3 inflammasome (NLRP3 and caspase-1) and IL-1β in galectin-3 treatment VSMCs, the protein and mRNA level of NLRP3, caspase-1, and IL-1β were observed by using Western blot and qRT-PCR respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In cardiovascular systems, TXNIP upregulation is related to hypertension and arterial stiffness [ 12 , 13 ]. TXNIP mediates the activation of NLRP3 inflammasome in macrophages [ 14 ]. VSMCs is the principal cellular components in the medial layer of arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Some ceramides present neutral or benign forms, while others are harmful species related to increased cardiovascular risk. Among these, direct impact on inflammation, promoting inflammasome activation and IL (interleukin)-1β release, 36 have been described; they also disrupt insulin signaling, 37 promote monocyte adhesion, 38 and LDL oxidation 39 and are associated with the formation of coronary plaques 40 among many other deleterious vascular effects. However, the source of these ceramides to the plaques is still a matter of discussion, being plasma LDL, 41 arterial wall cells 40,41 or human blood monocyte-derived macrophages among some of the proposed sources.…”
Section: Discussionmentioning
confidence: 99%